1998
DOI: 10.1080/00071669889484
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of clenbuterol and various concentrations of protein on performance of broiler chickens

Abstract: 1. The effects of the beta-adrenergic agonist, clenbuterol (1 mg/kg diet) on the growth and muscle composition in female broiler chickens (14 to 32 d of age) fed on diets containing various concentrations of protein (220, 240 or 260 g protein/kg) were examined. 2. Body weight gain over the 18 d period increased linearly with increasing protein intake. The rate of gain was significantly higher in clenbuterol-treated chickens than in control birds. 3. Dietary clenbuterol increased thigh muscle weight and protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Further, chickens have been shown to be insensitive to b-agonist administration (Weppelman, 1984;Wellenreiter, 1991). More recently, nutritional factors such as level of dietary protein and energy, and thiamin administration were shown indirectly to inhibit or improve the repartitioning impact of a b-agonist, clenbuterol, in chickens (Hamano et al 1994(Hamano et al , 1998(Hamano et al , 1999. Vitamins including LA that act as cofactors in enzyme systems catalysing metabolic processes might be prerequisites for enhancing the subsequent response to b-agonists in the tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, chickens have been shown to be insensitive to b-agonist administration (Weppelman, 1984;Wellenreiter, 1991). More recently, nutritional factors such as level of dietary protein and energy, and thiamin administration were shown indirectly to inhibit or improve the repartitioning impact of a b-agonist, clenbuterol, in chickens (Hamano et al 1994(Hamano et al , 1998(Hamano et al , 1999. Vitamins including LA that act as cofactors in enzyme systems catalysing metabolic processes might be prerequisites for enhancing the subsequent response to b-agonists in the tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although this vitamin has been shown to be associated with insulin and thyroid hormones (Segermann et al 1991;Streeper et al 1997), whether there is an interrelationship with b-adrenergic response is unclear. With regard to repartitioning nutrients in chickens, the metabolic response to b-agonist supplementation, which stimulates protein deposition and decreases adipose tissue accretion (Dalrymple et al 1984;Weppelman, 1984;Buyse et al 1991), is dependent on nutritional and hormonal states (Hamano et al 1994(Hamano et al , 1995(Hamano et al , 1998. In addition, the b-adrenergic response of leanness in chickens is thought to be generally weaker than that of mammals (Yang & McElligott, 1989;Wellenreiter, 1991).…”
mentioning
confidence: 99%
“…In domestic animals, clenbuterol (CLE), a selective b 2 -adrenergic agonist, is well known to be a potent growth promoter that increases muscle mass and protein deposition or decreases adipose tissue accretion [3,5,15,16,20]. Moreover, recent studies have reported that this repartitioning action is dependent upon nutritional states such as dietary protein level [2,6,7]. With regard to vitamins, thiamine supplementation enhances the lipolytic response of broiler chicks to CLE administration [8].…”
mentioning
confidence: 99%